Pendampingan “Comet” Pengawas Sekolah Melalui Digitalisasi Wordpress Untuk Meningkatkan Kreativitas Guru dan Tenaga Pendidik - Kusmawati, Ary (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2024)
This research aims to 1) increase the creativity of teachers and education staff in the learning process in target schools using the Comet approach via WordPress media. 2) Knowing the application of "School supervisor Comet via WordPress media can be used to increase the creativity of teachers and education staff in target schools. 3) Producing effective assistance through the implementation of "Comet school supervisors via WordPress media in target schools. The method used is descriptive qualitative using a word or behavior, and not expressed in the form of numbers or statistics. The research subjects were 11 assisted schools. Data collection techniques using observation, taking school response questionnaires. The results obtained from the media test were suitable for use, the responses obtained were very agreeable. The assistance provided is by using coaching and mentoring which is integrated into WordPress media. Coaching is exploring educational units to discover the potential of the coachee, while mentoring is guiding educational units to gain new knowledge. Based on the results of the change commitment mapping analysis, there was 1 school that used coaching, 5 schools had mentoring, 5 schools had coaching and mentoring. After all educational units have implemented this strategy, they are expected to play an active role in WordPress media, where this media is an online media that is used to learn together. So that understanding of the program and learning process can be carried out effectively. So the conclusion of this research is that the comet approach through WordPress media can increase the creativity of educational units by producing championships for both teachers and students. Apart from that, it also produces more effective and efficient assistance because educational units can learn independently using this media